Digital Therapeutics (DTx): Evaluating Efficacy in Chronic Disease Management (Digital Health & Telemonitoring Advances E: 3117-6461 | P: 3117-647X, 2026)
Digital Therapeutics (DTx) have emerged as a revolutionary approach in chronic disease management, providing evidence-based interventions through software programs and mobile applications. DTx solutions offer personalized, scalable, and continuous healthcare support, targeting conditions such as diabetes, cardiovascular diseases, chronic respiratory disorders, and mental health conditions. This paper evaluates the efficacy of DTx interventions in managing chronic diseases by examining clinical outcomes, patient adherence, behavioral modifications, and cost-effectiveness. Drawing from randomized controlled trials, meta-analyses, and real-world studies, the research highlights the transformative potential of DTx while addressing challenges related to accessibility, integration, regulatory approval, and long-term sustainability. Findings indicate that DTx interventions significantly improve disease management, patient engagement, and quality of life, though successful implementation requires robust clinical validation, technological infrastructure, and supportive healthcare policies.